Gender Similarity in the Use of and Attitudes About ALN in a University Setting - Ory, John C.; Bullock, Cheryl; Burnaska, Kristine (Online Learning, 1997)
This paper presents the results of an investigation of male and female student use of and attitudes about ALN after one year of implementation in a university setting. Results of the study revealed no significant gender differences.